Proceso administrativo del Centro de Atención Integral Kraaker en la ciudad de Babahoyo, periodo 2023. - Carrasco Moran, Lady Lisbeth (2024)
The present case study focused on the Administrative Process of the Kraaker Comprehensive Care Center in the city of Babahoyo, period 2023. Where the existing problem is due to the lack of optimal execution of the administrative process, which includes planning, organization, direction and control. This deficit directly affects the efficiency and effectiveness of the company’s operations. Therefore, the study aims to address the problem to ensure the development of the organization and highlight the importance of the administrative process in the operation of the company, examining different aspects such as strategic planning, the organizational structure and allocation of responsibilities, the determining role of management and motivation in the performance of the work team, and the influence of control on the evaluation of work efficiency. To ensure the proper preparation of the case study, a variety of research tools have been employed in order to identify areas of dissatisfaction among staff in relation to the internal processes of the company. In this sense, it is suggested that the Kraaker Comprehensive Care Center use the information gathered in this study to guide the development of new strategies and procedures that promote the administrative process effectively and efficiently in the organization. Implementing these recommendations could contribute significantly to improving the work climate and optimizing the overall performance of the company.